1996
DOI: 10.1046/j.1365-2567.1996.d01-773.x
|View full text |Cite
|
Sign up to set email alerts
|

Role of prolactin in the in vitro development of interleukin‐2‐driven anti‐tumoural lymphokine‐activated killer cells

Abstract: SUMMARYExogenous prolactin (PRL) has been shown to synergize with low-dose interleukin-2 (IL-2) and induce the proliferation and lymphokine-activated killer (LAK) maturation of natural killer (NK) cells. PRL itself can also generate LAK activity. Here we show that its local production occurs during, and is necessary for, LAK development. IL-2-stimulated peripheral blood mononuclear cells (PBMC) and purified NK cells were exposed to anti-human (h)PRL antiserum, and residual LAK activity was measured on day 7 ag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

1998
1998
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…This nding was unexpected since PRL secretion in lymphoid cells is both independent of Pit-1 and thought to be unaffected by other known regulators of pituitary PRL production. 43 Since it has been shown that PRL induces its own synthesis in human T-lymphocytes, 44 one possibility for this nding could be explained by a hormonal effect upon the immune system of the metoclopramidestimulated release of pituitary PRL. However, this metoclopramide effect in normal subjects, but not in SLE patients, deserves to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…This nding was unexpected since PRL secretion in lymphoid cells is both independent of Pit-1 and thought to be unaffected by other known regulators of pituitary PRL production. 43 Since it has been shown that PRL induces its own synthesis in human T-lymphocytes, 44 one possibility for this nding could be explained by a hormonal effect upon the immune system of the metoclopramidestimulated release of pituitary PRL. However, this metoclopramide effect in normal subjects, but not in SLE patients, deserves to be further investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Purified NK cells were isolated from peripheral blood of normal donors, as previously described. 6 PBMC were obtained after separation of heparinized blood of normal donors on Ficoll–Hypaque. NK‐enriched cell populations consisting of > 70% CD16 + CD56 + , < 2% CD3 + cells were obtained from PBMC after depletion of monocytes by adherence on plastic flasks, depletion of B cells by passage on a nylon wool column and depletion of high‐affinity E‐rosette‐forming cells (E Ha ), as previously described.…”
Section: Methodsmentioning
confidence: 99%
“…In addition, interleukin (IL)‐2‐driven lymphokine‐activated killer (LAK) maturation of natural killer (NK) cells, present in peripheral blood mononuclear cells (PBMC), has been shown to depend on endogenously produced PRL. 6 When added to purified NK cells 7 , 8 or to PBMC, 9 PRL has been shown to mimic IL‐2‐induced cell growth, 8 NK enhancement and LAK development. 7–9 PRL and IL‐2 receptors belong to the family of haemopoietin class I receptors 10 , 11 and share downstream intracellular signalling pathways 12 , 13 and, possibly, target genes.…”
Section: Introductionmentioning
confidence: 99%
“…Suboptimal concentrations of the hormone synergize with IL-2 to augment in vitro activation [71,84], but concentrations 5-10 times higher than physiological levels are inhibitory [70]. Physiological concentrations of PRL stimulate the activity and increase DNA, RNA and protein synthesis in purified NK cells, whereas higher levels of the hormone have been associated with decreased NK activity [85].…”
Section: Neuroendocrine Effects On Nk Cellsmentioning
confidence: 99%